Differences in Numeration Literacy Abilities and Interest in Using PBL and Cognitive Growth Learning Models in Primary School Students - Farhatun Trisna Adilla (Randwick International of Education and Linguistics Science Journal, 2023)
It would discuss differences in the numeracy literacy abilities of students who are taught using PBL and students who are taught using the cognitive growth learning model and Differences in students’ learning interest in PBL model with students taught using the cognitive growth learning model. The research method is used a quasi-experiment which aim to see the differences. The result show that there is actually no difference in the knowledge formation process carried out in PBL and Cognitive Growth learning, students are required to be more active in the learning process and the learning model is the main effect that influence the increase in students’ literacy skills and learning interest.